2014
DOI: 10.12980/apjtb.4.2014c701
|View full text |Cite
|
Sign up to set email alerts
|

Screening of antiangiogenic potential of twenty two marine invertebrate extracts of phylum Mollusca from South East Coast of India

Abstract: The significant antiangiogenic activity evinced by the extract of Telescopium telescopium merits further investigation for ocular neovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In a recent study, Bojnourdi et al [ 20 ] investigated the anti-angiogenic properties of shell extract of the mollusc chiton on CAM model and found that it produced maximum 58% anti-angiogenic activity. In another interesting study by Gupta et al [ 21 ], 22 different marine invertebrate extracts were screened for their anti-angiogenic activity, out of which, Meretrix meretrix (47.01% inhibition), Meretrix casta (64.63% inhibition), Telescopium telescopium (62.02% inhibition) and Bursa crumena (60.48% inhibition) showed significant anti-angiogenic activity in CAM. In the present study, EAME showed 42% inhibition of branching points and 51% inhibition of first order blood vessels in CAM (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Bojnourdi et al [ 20 ] investigated the anti-angiogenic properties of shell extract of the mollusc chiton on CAM model and found that it produced maximum 58% anti-angiogenic activity. In another interesting study by Gupta et al [ 21 ], 22 different marine invertebrate extracts were screened for their anti-angiogenic activity, out of which, Meretrix meretrix (47.01% inhibition), Meretrix casta (64.63% inhibition), Telescopium telescopium (62.02% inhibition) and Bursa crumena (60.48% inhibition) showed significant anti-angiogenic activity in CAM. In the present study, EAME showed 42% inhibition of branching points and 51% inhibition of first order blood vessels in CAM (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On the 14th day, percentage inhibition of neovascularization was seen after enucleating the animals. Rats were anesthetized and sacrificed; the eyes were removed to check for inhibitory effect [12].…”
Section: Corneal Neovascularization Methodsmentioning
confidence: 99%
“…U. reticulata presented the maximum contents of chromium, copper and magnesium. At the same time, Halimeda tuna only exhibited low mineral contents of cobalt, iron, magnesium, manganese, nickel, lead and zinc (Gokulkrishnan et al, 2011). Besides, C. lentillifera from the Kei Islands of Indonesia contained magnesium, potassium and zinc, whereas C. lentillifera from the Seribu Islands contained calcium (119.20 g/kg), sodium (34.18 g/kg) and iron (0.34 g/kg), respectively (Tapotubun et al, 2020).…”
Section: Mineralsmentioning
confidence: 97%
“…Seafood, including seaweed species, are usually known to hold an abundance of minerals such as iodine, magnesium, calcium, phosphorus, iron, potassium, copper and fluoride (Gokulkrishnan, Anantharaman, Manivannan, Thirumaran, & Balasubramanian, 2011). These minerals play a significant role as a cofactor of the enzyme in the human body.…”
Section: Mineralsmentioning
confidence: 99%
See 1 more Smart Citation